Konstruksi Nilai Nasionalisme dalam Bait Sya’ir Tanpo Waton (Analisis Semiotik Model Ferdinand De Saussure) - M. Sabron Sukmanul Hakim (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2019)
Each song has its own message, both worldly and ukhrawi's message. This study aims to find out how the construction of the values of nationalism in the verse